Peran Guru dalam Penanaman Nilai Karakter Religius di Lingkungan Sekolah pada Siswa Sekolah Dasar - Ahmad Hariandi; Yanda Irawan (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
The purpose of this study was to find out the value of religious character in the school environment in class IV SDN NO 20 / I Jembatan Mas. This study used descriptive qualitative method. The implementation of this research was in SD Negeri 20 / I Jembatan Mas. Administratively it entered the Pemayung District of Batanghari Regency. Data collection is done by observation, interview, and documentation techniques. Data analysis techniques are done by data reduction, data presentation, and conclusion drawing. The conclusion of this study is the role of the teacher in planting religious character in the school environment for fourth grade students SDN No.20 / I Jembatan Mas has sought to maximize using the role as an educator while acting as a teacher, both inside and outside the class and has been categorized well. By means of spending time to pray in congregation with discipline and discipline in the mosque, good manners to speak between students, students and teachers, dressing close to genitals, cultivating smiles, greetings and greetings, pairing the work of students in the form of photos and motto containing messages religious values. but it is expected that the need for participation is not only from the implementation but also the support of the role of the family and the community around the students need to be considered. In religious values ​​can also be contained in the form of; the spirit of sacrifice, caring for others, helping each other, the behavior of the tradition of prayer in congregation, love to pray, diligent study and other noble behavior.